2018
DOI: 10.1155/2018/9037657
|View full text |Cite
|
Sign up to set email alerts
|

IsolatedSporothrix schenckiiMonoarthritis

Abstract: Sporothrix schenkii sensu lato is a rare cause of arthritis. Its course is indolent with lack of constitutional symptoms resulting in delayed presentation and diagnosis. It is a dimorphic fungus found ubiquitously in sphagnum moss, decaying vegetation, soil, and hay. Inoculation of dirt into the skin and soft tissues and, in rare instances, inhalation of aerosolized conidia from soil and plants can lead to infection. Subacute and chronic involvement of skin and subcutaneous tissues is the most common manifesta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 27 publications
(35 reference statements)
0
11
1
Order By: Relevance
“…Initial manifestations are tenosynovitis, joint effusion, bursitis, and synovial cyst formation [ 8 ]. The time to diagnosis in our case was 6 months; it seems earlier than this reported in previously cases [ 5 , 9 , 10 ]. Due to this early diagnosis of Sporothrix schenkii infection, there are no extensive destructive changes which occur in the affected joints because of delayed diagnosis.…”
Section: Discussioncontrasting
confidence: 46%
See 1 more Smart Citation
“…Initial manifestations are tenosynovitis, joint effusion, bursitis, and synovial cyst formation [ 8 ]. The time to diagnosis in our case was 6 months; it seems earlier than this reported in previously cases [ 5 , 9 , 10 ]. Due to this early diagnosis of Sporothrix schenkii infection, there are no extensive destructive changes which occur in the affected joints because of delayed diagnosis.…”
Section: Discussioncontrasting
confidence: 46%
“…The cutaneous and lymphocutaneous forms of sporotrichosis are the most common forms of clinical presentation. Osteoarticular lesions are rare, representing 3–4% of cases [ 5 ], and particularly affect immunocompromised, alcoholic and diabetic patients [ 6 , 7 ]. However, our case has no immunosuppression factor.…”
Section: Discussionmentioning
confidence: 99%
“…A total of 48 publications related to sporotrichosis were found in North America [ 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 ]. There were 1460 patients in total associated with infection caused by species of the genus Sporothrix .…”
Section: Epidemiology Of Sporotrichosis In North Americamentioning
confidence: 99%
“…According to the previous classification, it was found that in Canada, only two case reports were found, one from Ontario and the other from Toronto [ 5 , 6 ]. In the US, 27 reports containing 1 clinical case were found (81.5% S. schenckii , 18.5% Sporothrix spp., S. schenckii complex, and S. schenckii sensu lato ) [ 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 ]. Of these, seven cases came from California, three from Oklahoma, two cases from Kansas, Texas, Arizona, Minnesota, and Florida, one case from Michigan, Nebraska, Oregon, Pennsylvania, and finally, one case without a specific city or region.…”
Section: Epidemiology Of Sporotrichosis In North Americamentioning
confidence: 99%
See 1 more Smart Citation